Icons of style : in 100 garments - Sims, Josh (Laurence King, an imprint of the Orion Group Publishing Group Ltd., 2024)
"Behind nearly every item in the modern wardrobe is a 'first of its kind' - the definitive item, often designed by a single company or brand for specialist use, on which all subsequent versions have been based (and originals of which are now collector items in the booming vintage market). The T-shirt, for example, may now be an innocuous, everyday item, but was created by American company Hanes for US Navy personnel at the turn of the 20th century and was subsequently adopted by sportsmen and bikers. Other items have been designed for sport, farm work or protection, and made their way into everyday usage. Icons of Style examines, garment by garment, the most important and famous of these products - their provenance and history, the stories of their design, the brand/company that started it all and how the item shaped the way we all dress today. As traditional definitions of men's and women's clothes are fast changing, this book combines all key garments for everyone. Inspiring images of the best examples of the garment - from the 1930s to contemporary times, from Marlene Dietrich to Mick Jagger - show the timeless beauty of these garments that are the basics of the stylish."--Amazon.com.